The Effect Of Virtual Physical Exercise On Body Mass Index And Waist Circumstances Of Students Faculty Of Medicine - Budisusilo, Wawan; Ujianti, Irena; Pangestu , Mulyoto (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2024)
One of the most often utilized measures in calculating body proportion criterion is the BMI. The goal of this study is to see if there is a link between BMI and glucose levels in students who are given virtual physical activity. A high sedentary lifestyle is thought to be linked to the high prevalence of metabolic disorders among students. A rise in BMI or waist circumference levels indicates that a person may be at risk for a variety of metabolic disorders as a result of body mass index. An experimental study was utilized to investigate if there was a difference in the respondents' body mass index and waist circumference before and after the intervention. Before and after the treatment, there were significant variations in waist circumference (76.921.51 vs 74.651.47 cm, p0.001) and BMI (23.540.76 vs 23.050.77 cm, p0.001). Furthermore, with a value of r=0.895 and p0.001, there is a high link between BMI and waist circumference.